Delegating Pricing Authority to Sales Agents: The Impact of Kickbacks - Kräkel, Matthias; Schöttner, Anja (Management Science, 2020)
We investigate a situation where a firm employing a sales agent faces moral hazard with respect to prospecting effort and the threat of collusion between agent and customer. We show that the firm should offer more pricing authority to the agent the more severe the moral hazard problem, although doing so further expands the agent’s discretion. Nevertheless, restricting the agent’s pricing authority such that he cannot sell to low-valuation customers is typically optimal to prevent collusion. We derive optimal collusion-proof contracts, describe conditions under which collusion arises in equilibrium, and study the optimal interaction between delegation, incentive pay, and the firm’s installed auditing technology. This paper was accepted by Juanjuan Zhang, marketing.